2002
DOI: 10.1021/la020183y
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated Structures of Rhodamine 6G Intercalated in a Fluor-Taeniolite Thin Film

Abstract: To clarify the structure and species of rhodamine 6G (R6G) aggregates formed in taeniolite (TN) interlayer spaces, the oriented thin films of R6G-TN hybrid materials were prepared and analyzed. XRD investigations of these films indicated that the R6G molecules were intercalated in the TN interlayers and that the TN layers were parallel to the glass plate in the thin films. Most of the intercalated R6G molecules were assumed to form various kinds of H-type aggregates in the TN interlayer spaces, since the R6G-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
113
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 41 publications
11
113
0
1
Order By: Relevance
“…The sample that has been stored in air for three weeks still exhibits high and comparable sensitivity to the fresh substrate. For clarity, the spectra are offset along the y-axis.required for an adsorbed CV molecule is taken to be approximately 0.4 nm 2 in case of perpendicular orientation[26] with a long-axis length of about 1.4 nm[27]. The N bulk , under the area of laser spot (∼10 m in diameter and 2 m in penetration depth) can be accordingly calculated to be 2.8 × 10 11 molecules; {N bulk = × 25 × 2 m 3 /(0.4 × 1.4 nm 3 )}.…”
mentioning
confidence: 99%
“…The sample that has been stored in air for three weeks still exhibits high and comparable sensitivity to the fresh substrate. For clarity, the spectra are offset along the y-axis.required for an adsorbed CV molecule is taken to be approximately 0.4 nm 2 in case of perpendicular orientation[26] with a long-axis length of about 1.4 nm[27]. The N bulk , under the area of laser spot (∼10 m in diameter and 2 m in penetration depth) can be accordingly calculated to be 2.8 × 10 11 molecules; {N bulk = × 25 × 2 m 3 /(0.4 × 1.4 nm 3 )}.…”
mentioning
confidence: 99%
“…These spectra showed that the gradient of changes as induced by the polarized light was much higher for polarisation in the x direction than in the y direction. This anisotropy is caused by the orientation of the dye transition moment with respect to the plane surface of montmorillonite upon its adsorption (Sasai et al, 2002). It should be pointed out that when C522 was used for the film modification in the MF-C522 10 −6 sample, no absorbance band for this dye could be detected in the prepared MF sample (Fig.…”
Section: Spectral Properties Of Montmorillonite Filmsmentioning
confidence: 99%
“…2). The technical details were published by Sasai et al (2002). Briefly, the orientation of the slide during measurements was changed around the x-axis at angles α with respect to the y-axis only, with tilt angles α = 0, 40, 50, 60 and 70°.…”
Section: Preparation and Characterisation Of Optically Active 2d Filmsmentioning
confidence: 99%
See 2 more Smart Citations